MASS STRANDING OF PILOT WHALES IN THE GULF OF MANNAR - Alagarswami, K; Bensam, P; Rajapandian, M E; Fernando, A Bastian (Indian Journal of Fisheries, 2011)
Many Indian pilot whales, Globicephala macrorhyncha, were stranded in a shallow bay in the Gulf-of Mannar at Manapad on 14 January 1973. This is the second recorded instance of stranding of pilot whales ou the Indian coasts, in which a casualty of 147 individuals is involved; the earlier one was at Serampore on the Hooghly River. The dead whales had a size range "of 220-575 cm. General morphological and diagnostic skeletal features of the pilot whales are given and discussed. Autopsy and chemical examination proved neptive for the presence of poisonous substances in the tissues of the stranded animals. The mass stranding at Manapad is discussed with reference to similar phenomenon among the pilot whales noticed in other parts of the world